1981
DOI: 10.1037/0278-7393.7.3.227
|View full text |Cite
|
Sign up to set email alerts
|

Thematic contribution to overgeneralization in memory for quantified discourse.

Abstract: The present study examines whether overgeneralization of the quantified relations in a story reflects reasonable inferences from the story's theme. Subjects were asked to read narratives with similar story structures but with different thematic conflicts. Two-choice recognition results showed that overgeneralization "errors" are systematic, consistent with thematic elements of the narrative, and induced by thematic inferences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1988
1988
1988
1988

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Owens et al found that the thematic statement not only improved memory for the scripts (see also Wyer, Srull, Gordon, & Hartwick, 1982), but it also increased the likelihood of false recognition of theme-appropriate script information and reduced false recognitions of theme-inappropriate statements as well. It has also been shown that thematic information increases false recognitions of theme-relevant items over extended periods of time (Christiaansen, 1980; Dooling & Christiaansen, 1977; Revlin, Bromage, & Van Ness, 1981) apparently because the representation of the original material is less accessible over time and people must rely on their generic knowledge of the theme to remember the text.…”
mentioning
confidence: 99%
“…Owens et al found that the thematic statement not only improved memory for the scripts (see also Wyer, Srull, Gordon, & Hartwick, 1982), but it also increased the likelihood of false recognition of theme-appropriate script information and reduced false recognitions of theme-inappropriate statements as well. It has also been shown that thematic information increases false recognitions of theme-relevant items over extended periods of time (Christiaansen, 1980; Dooling & Christiaansen, 1977; Revlin, Bromage, & Van Ness, 1981) apparently because the representation of the original material is less accessible over time and people must rely on their generic knowledge of the theme to remember the text.…”
mentioning
confidence: 99%